Model Regresi Moderasi pada Hubungan Kecemasan Matematika dan Kompetensi Statistika Mahasiswa - Yusrina Nur Dianati; Dewi Kurnia Sari; Dewi Susanawati (Universitas Ma'arif Lampung, 2026)
This research aims to examine the effect of mathematics anxiety on students’ statistical competence, the influence of mathematics self-efficacy on statistical competence, and the moderating role of self-efficacy in the relationship between these two variables. The study employed a quantitative approach with an explanatory research design. The participants consisted of 93 undergraduate students enrolled in a statistics course in a mathematics education program. Data were collected using a Likert-scale questionnaire and analyzed through Moderated Regression Analysis (MRA) with mean-centering and bootstrapping techniques. The findings indicate that mathematics anxiety does not have a significant direct effect on statistical competence, whereas mathematics self-efficacy has a positive and significant effect. Furthermore, self-efficacy significantly moderates the relationship between mathematics anxiety and statistical competence by weakening the negative impact of anxiety. These results suggest that self-efficacy functions as a protective factor in statistics learning. Therefore, strengthening students’ self-efficacy should be a key consideration in designing effective statistics instruction.